Amplification of 200-ps high-intensity laser pulses via frequency matching stimulated Brillouin scattering. (2019) - Yuan, Hang; Wang, Yulei; Yuan, Qiang; Hu, Dongxia; Cui, Can; Liu, Zhaohong; Li, Sensen; Chen, Yi; Jing, Feng; Lü, Zhiwei
Abstract : Laser pulses of 200 ps with extremely high intensities and high energies are sufficient to satisfy the demand of shock ignition, which is an alternative path to ignition in inertial confinement fusion (ICF). This paper reports a type of Brillouin scheme to obtain high-intensity 200-ps laser pulses, where the pulse durations are a challenge for conventional pulsed laser amplification systems. In the amplification process, excited Brillouin acoustic waves fulfill the nonlinear optical effect through which the high energy of a long pump pulse is entirely transferred to a 200-ps laser pulse. This method was introduced and achieved within the SG-III prototype system in China. Compared favorably with the intensity of $2~\text{GW}/\text{cm}^{2}$ in existing ICF laser drivers, a 6.96- $\text{GW}/\text{cm}^{2}$ pulse with a width of 170 ps was obtained in our experiment. The practical scalability of the results to larger ICF laser drivers is discussed.